Risk Factors for Depression in Pregnancy: Scoping Review - Catur Setyorini; Ismarwati Ismarwati; Mamnuah Mamnuah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Antenatal depression has become a common and serious problem that can affect the health of both mother and baby. This study aims to review the latest obstetric scientific evidence on the risk factors for depression in pregnancy. This research is a Scoping review using the Arkshey and O'Malley Framework and the PRISMA-ScR Checklist. The literature search used 3 databases, namely Pubmed, Science Direct, and Wiley Online Library. The keywords used were pregnant women, risk factors, and pregnancy depression. The inclusion criteria were original articles; published in 2018 to 2022, in English, open access and full text, and a focus on risk factors for pregnancy depression. Article quality assessment uses the Joanna Briggs Institute (JBI) Checklist. 13 articles were quantitative studies conducted in hospitals and clinics, and came from 8 different countries. Mapping themes from the results of the article analysis are the prevalence of depression in pregnancy, risk factors based demographics including age, education level, marital status and occupation, risk factors based on obstetric characteristics including the number of pregnancies, history of abortion, unwanted pregnancies and diseases in pregnancy, as well as risk factors based on psychosocial including husband support, family, domestic violence, and harmful habits. Information on recognizing risk factors for depression in pregnancy is important for health workers to detect depression on time and implement relevant psychosocial interventions to reduce the incidence of depression during pregnancy. Abstrak: Depresi antenatal telah menjadi masalah umum dan serius yang dapat mempengaruhi kesehatan ibu dan bayinya. Penelitian ini bertujuan meninjau bukti ilmiah kebidanan terbaru tentang faktor-faktor resiko yang menyebabkan terjadinya depresi pada kehamilan. Penelitian ini merupakan Scoping review dengan menggunakan Arkshey dan O'Malley Framework dan PRISMA-ScR Checklist. Pencarian literatur menggunakan 3 database yaitu Pubmed, Science Direct dan Wiley Online Library. Kata kunci yang digunakan adalah ibu hamil, faktor resiko dan depresi kehamilan. Kriteria inklusi adalah original artikel, terbit tahun 2018 hingga 2022, bahasa Inggirs, open akses dan full teks serta fokus pada faktor resiko depresi kehamilan. Penilaian kualitas artikel menggunakan Ceklist Joanna Briggs Institute (JBI). Didapatkan 13 artikel yang merupakan penelitian kuantitatif dilakukan di rumah sakit dan klinik, serta berasal dari 8 negara berbeda. Pemetaan tema dari hasil analisis artikel adalah prevalensi depresi dalam kehamilan, faktor resiko berdasar demografi meliputi umur, tingkat pendidikan, status pernikahan dan pekerjaan, faktor resiko berdasar karakteristik obstetri meliputi jumlah kehamilan, riwayat abortus, kehamilan tidak diinginkan dan penyakit dalam kehamilan, serta faktor resiko berdasar faktor psikosocial meliputi dukungan suami, keluarga, kekerasan dalam rumah tangga serta kebiasaan yang merugikan. Pengetahuan dalam mengenali faktor risiko depresi kehamilan penting bagi tenaga kesehatan mendeteksi depresi secara tepat waktu dan menerapkan intervensi psikososial yang relevan untuk mengurangi kejadian depresi selama kehamilan.